O processo de mudança na Demelfor S.A: um estudo de caso no setor orizicola uruguaio - Beck, Anderson de Medeiros (2008)
This study deals with the change process in an interprise of the rice growing sector, whose headquarter is located at the Artigas Department, Uruguay, in the period 1990-2007. It is a qualitative study case, based on pre-structured interviews with six directors, allowing us to describe and analyse the main strategic changes and structures undergone by the company under the view of eight key-questionings: dominant coalition formation, establishment of a view of the future, communication in the organization, formation of a team to implement the change, mobilization promotion and members participation, planning and strategies specification, capacitation and human resources development and finally definition of performance indicators. Other studies focusing on human resources and their role in conducting the change process, and also studies on operational and tactic strategic indicators, developing the instrument to measure the performance, and a study of the organizational change departing from the utilization of the performance indicators.